Control Systems Group, Department of Department of Electrical, Electronic and Computer Engineering, University of Pretoria, South Africa [Institutes in Control] - Craig, Ian; Sepulchre, Rodolphe (IEEE control systems, 2024)
In this issue, we talk with Ian Craig and Derik le Roux about the activities of the Control Systems Group in the Department of Electrical, Electronic and Computer Engineering (DEECE) at the University of Pretoria (UP), South Africa. Ian is the current group head and was featured in one of the early IEEE Control Systems (CSM) columns on "People in Control" [S1]. Derik joined the group in 2016 and is currently an associate professor in the DEECE.